Nutritional and haemato-biochemical modulation in dairy goats during mid-pregnancy - KUMAR, AJIT; PATTANAIK, A K; BALIYAN, SHALINI; DUTTA, NARAYAN; JADHAV, S E (The Indian Journal of Animal Sciences, 2018)
The present study was conducted to assess the influence of mid-pregnancy on the nutrient utilization, haematological and blood biochemical profile in gravid goats. Sixteen indigenous non-descript does of approximately 3–4 years of age were randomly allotted to two equal groups (PREG and NPREG) of eight each based on individual BW. The goats of pregnant group (PREG) were synchronized, mated and were left for routine group feeding, care and management. They were brought to experiment just 60 days after mating along with the non-pregnant (NPREG) group; both the groups were offered basal diet comprised of concentrate mixture and wheat straw to meet their nutrient requirements. A metabolic trial of six day duration was conducted at 90 days after mating on all the experimental goats to assess the nutritional modulation along with any changes of haematological and blood biochemical parameters at mid pregnancy stages. The results revealed no variation in intake and digestibility of DM, OM and CP. However, the digestibility of NDF, ADF and hemicellulose was higher for PREG does as compared to NPREG control. The balance of nitrogen was positive and comparable between the groups. Blood haematobiochemical profile showed no significant influence of pregnancy on different blood metabolites except that of low serum urea. The serum variables representative of the liver function was within the normal range and were comparable between the groups. It is concluded that mid-pregnancy induces no perceptible nutritional modulation except for subtle improvements in fibre digestibility, and possibly protein utilization in dairy goats.